THE PRINCIPLE OF FREEDOM OF CONTRACT IN PROCUREMENT OF GOODS AND SERVICES AGREEMENT BETWEEN COMMITMENT MAKING OFFICER AND PROVIDER (STUDY AT THE OFFICE OF PUBLICS WORK OF SIJUNJUNG REGENCY) - Aditya, Dimas; Oktarina, Neneng (UNES Journal of Swara Justisia, 2019)
One of the basic principles of contract law is the principle of Freedom of Contract.As the name implies, the principle dictates that private or public individuals and groupsare free to form contracts without any restriction. As free as it is, the principle howeverdoes have some restriction, In the Indonesia Civil Code (Kitab Undang-Undang HukumPerdata) there are some provisions that limits such freedom. Article 1320 of IndonesiaCivil Codes stipulates four conditions to be fulfilled in order an agreement to be valid.Others limitation could come from any other laws and regulations such as the PresidentialRegulation Number 16 of 2018 Regarding The Government’s Procurement Of Goods andServices. The principle of freedom of contract bestows a great number of authorities to theCommitment Making Officer in terms of making procurement agreements with provider.However, such authority doesn’t go as well in practice, breach of contract and abuse ofpower by the officer are some of the common problems in the government’s procurement.This thesis analyzes those problems, specifically that indicates corruption in theprocurements by the Office of Public Work of Sijunjung Regency.